1996
DOI: 10.1128/jb.178.2.372-376.1996
|View full text |Cite
|
Sign up to set email alerts
|

Cell-to-cell signaling in the symbiotic nitrogen-fixing bacterium Rhizobium leguminosarum: autoinduction of a stationary phase and rhizosphere-expressed genes

Abstract: The Sym plasmid pRL1JI encodes functions for the formation of nitrogen-fixing pea root nodules by Rhizobium leguminosarum. Some of the nodulation genes are involved in recognition of chemical signals produced by the plant root, and others are required for production of chemical signals recognized by the plant. pRL1JI also contains a regulatory gene, rhiR, that is homologous to luxR, the transcriptional activator of luminescence genes in Vibrio fischeri. LuxR requires a signal compound, an autoinducer, for its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
127
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(133 citation statements)
references
References 19 publications
5
127
1
Order By: Relevance
“…Strikingly, the luxI 1 mutant loses morphological heterogeneity and shows a faster growth rate than the wild type. This is in contrast to previous work showing growth inhibition by an autoinducer (Gray et al, 1996). Recently, it was observed that QS can induce gas vesicle formation in Serratia sp.…”
Section: Discussioncontrasting
confidence: 55%
“…Strikingly, the luxI 1 mutant loses morphological heterogeneity and shows a faster growth rate than the wild type. This is in contrast to previous work showing growth inhibition by an autoinducer (Gray et al, 1996). Recently, it was observed that QS can induce gas vesicle formation in Serratia sp.…”
Section: Discussioncontrasting
confidence: 55%
“…The extracts were also tested with the P. aeruginosa las and rhl bioassays to determine if any of the mutant LuxI polypeptides synthesized an acylated-homoserine lactone other than N-(3-oxohexanoyl)homoserine lactone. The las bioassay can be used to detect 3-oxoacylhomoserine lactones with 8 to 14 carbons in the acyl chain (11,19), and the rhl bioassay can be used to detect butyryl or hexanoylhomoserine lactone (16,20). In addition to N-(3-oxohexanoyl)homoserine lactone, wild-type LuxI produces smaller quantities of hexanoylhomoserine lactone and N-(3-oxooctanoyl)homoserine lactone (reference 15 and unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…AHL-mediated quorum sensing plays a role in regulating antibiotic biosynthesis (Wood et al, 1997), bioluminescence , plasmid conjugal transfer Piper et al, 1993), swarming , cessation of cell growth (Gray et al, 1996;Schripsema et al, 1996) and capsular polysaccharide synthesis (Beck von Bodman and Farrand, 1995). In Serratia sp.…”
mentioning
confidence: 99%